Positive Solutions of a Generalized Nonautonomous Fractional Differential System - Mohammed S. Abdo; Heba Y. Zahran; El Sayed Yousef; Emad E. Mahmoud; Abdel-Haleem Abdel-Aty (Journal of Mathematics)
In this work, we investigate the existence and uniqueness of positive solutions to a system of nonautonomous fractional differential equations. The fractional derivative of the system at hand is ψ- Riemann–Liouville fractional derivative. Some significant properties of this derivative that assist in the analysis of our results substantial are proved. The analysis is based on Guo-Krasnoselskii’s and Banach’s fixed point theorem. Finally, we give two examples to verify our results.